Education of Fish Detection Tools (Fish Finder) to Fishermen in Dusun XI Percut Sei Tuan Village, Deli Serdang Regency - Manurung, Vindy Rilani; Khairunnisa; Siregar, Rizky Febriansyah; Dewinta, Astrid Fauziah; Hasibuan, Julia Syahriani (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Traditional fishermen in Dusun XI, Percut Village, Deli Serdang Regency, North Sumatra Province, using rawai fishing gear, nets, and hand line instead of other technological gear. Sea tides also influence fisherman's ability to get out of sea; when the river mouth reaches high tides, fishermen will go to sea; when the river mouth recedes, fishermen can not go to sea. Fishermen are frequently returned to sea with little results, especially in the absence of technological application. Education is important, and advances in fish finder technology can help fishermen catch more fish by making it easier to use. The implementation method is theoretical and practical, with the formation of an actually trying to implement committee team occurrence through educational methods with theoretical media attention, as well as practical activities such as fisherman group discussions and joint operation demonstration activities in the field. Fishermen in Dusun XI, Percut Village, Deli Serdang Regency benefit significantly from using a fishfinder tool and helping in increasing fish catches, according to data monitoring and assessment.